Four-star movies the 101 greatest films of all time - Kinn, Gail; Piazza, Jim (New York, New York Black Dog & Leventhal Publishers, Inc., 2003)
Presents the authors' selections for the top 101 motion pictures of all time, each with comments on why the film was selected, background on the movie, a plot summary, profiles of the main actors, a cast list, credits, behind-the-scenes anecdotes, award nominations and wins, photographs, director comments, and quotes from critics.
1 Godfather I and II 10 -- 2 Casablanca 17 -- 3 Citizen Kane 20 -- 4 Gone with the Wind 23 -- 5 Lawrence of Arabia 26 -- 6 North by Northwest 29 -- 7 The Wizard of Oz 32 -- 8 Annie Hall 35 -- 9 Chinatown 38 -- 10 Singin' in the Rain 41 -- 11 Nashville 44 -- 12 Some Like It Hot 47 -- 13 All About Eve 50 -- 14 Psycho 53 -- 15 Taxi Driver 56 -- 16 Apocalypse Now 59 -- 17 On the Waterfront 63 -- 18 The Graduate 66 -- 19 Sunset Boulevard 69 -- 20 The Searchers 72 -- 21 La Dolce Vita 75 -- 22 Double Indemnity 78 -- 23 The Manchurian Candidate 81 -- 24 Vertigo 84 -- 25 Close Encounters of the Third Kind 87 -- 26 GoodFellas 90 -- 27 Jules and Jim 93 -- 28 Funny Face 96 -- 29 A Streetcar Named Desire 99 -- 30 Saving Private Ryan 102 -- 31 Strangers on a Train 105 -- 32 It Happened One Night 108 -- 33 One Flew Over the Cuckoo's Nest 111 -- 34 It's a Wonderful Life 114 -- 35 Raging Bull 117 -- 36 The Best Years of Our Lives 120 -- 37 The African Queen 123 -- 38 Dr. Strangelove 126 -- 39 Blade Runner 129 -- 40 The Conformist 132 -- 41 Schindler's List 135 -- 42 The Shawshank Redemption 138 -- 43 Diner 141 -- 44 The Deer Hunter 144 -- 45 The Bridge on the River Kwai 147 -- 46 8 1/2 150 -- 47 Top Hat 153 -- 48 Rules of the Game 156 -- 49 2001: A Space Odyssey 159 -- 50 Bonnie and Clyde 162 -- 51 King Kong 165 -- 52 Star Wars 168 -- 53 The 400 Blows 171 -- 54 A Night at the Opera 174 -- 55 My Fair Lady 177 -- 56 Terminator 2: Judgment Day 180 -- 57 The Third Man 183 -- 58 Doctor Zhivago 186 -- 59 ET: The Extra-Terrestrial 189 -- 60 Invasion of the Body Snatchers 192 -- 61 Pinocchio 195 -- 62 Butch Cassidy 198 -- 63 Fargo 201 -- 64 Blue Velvet 204 -- 65 Jaws 207 -- 66 The Grapes of Wrath 210 -- 67 Do the Right Thing 213 -- 68 Wild Strawberries 216 -- 69 The Bicycle Thief 219 -- 70 Bringing up Baby 222 -- 71 Paths of Glory 225 -- 72 The Maltese Falcon 228 -- 73 Pather Panchali 231 -- 74 The Lady Eve 234 -- 75 The Last Picture Show 237 -- 76 Raise the Red Lantern 240 -- 77 Rosemary's Baby 243 -- 78 Midnight Cowboy 246 -- 79 M*A*S*H 249 -- 80 American Graffiti 252 -- 81 The Producers 255 -- 82 Rashomon 258 -- 83 Cabaret 261 -- 84 The Bank Dick 264 -- 85 A Place in the Sun 267 -- 86 Red River 270 -- 87 The Conversation 273 -- 88 Grand Illusion 276 -- 89 L.A. Confidential 279 -- 90 Saturday Night Fever 282 -- 91 Imitation of Life 285 -- 92 Raiders of the Lost Ark 288 -- 93 Spartacus 291 -- 94 Belle de Jour 294 -- 95 The Seven Samurai 297 -- 96 A Hard Day's Night 300 -- 97 Atlantic City 303 -- 98 American Beauty 306 -- 99 Pulp Fiction 309 -- 100 Thelma and Louise 312 -- 101 Airplane 315.
Includes index.
Keywords: Motion pictures -- United States -- Plots, themes, etc; Motion pictures -- Plots, themes, etc